'Picture perfect' landscape stories: normative narratives and authorised discourse. (17th February 2022) - Hodsdon, Laura
ABSTRACT: Despite the positive impacts of an increasing number of organisational initiatives and campaign groups, unequal access to the countryside remains an intransigent issue. Contesting the countryside's normative associations is thus not just a conceptual challenge but a practical one for organisations managing rural sites. Taking the National Trust-run site of Wembury in Devon, UK, as a case study, I use critical discourse analysis to uncover institutions' (including the National Trust and other charities, news media, and factual programmes) and individuals' (using TripAdvisor data) discursive constructions of the landscape. Emerging themes include discourses of place, activities, and people, that—despite some dissonance and seeming contestation—cohere and (re)produce ideologies based on normative narratives of rural landscapes. I suggest the potential value of discourse analysis in surfacing rural storyscapes, and leveraging them to disrupt discourses which further exclusionary ideologies, as a tool to enable locally contextualised, practical means of advancing inclusion.